Analisa Tingkat Kepuasan Penggunaan Laboratorium Komputer Menggunakan Service Quality pada STMIK Widuri - Andika Purnama; Rouli Doharma (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
An effective learning process highly depends on the quality of available facilities, including computer laboratories. This study aims to analyze student satisfaction at STMIK Widuri regarding the use of computer laboratories by employing the SERVQUAL method. Data collection methods included interviews, observations, questionnaires, and literature studies, with a total of 54 respondents from the Information Systems and Computer Engineering programs. The results revealed that students reported various issues, such as network disruptions and malfunctioning equipment. The quality of service measurement indicated negative gap values across all dimensions, including tangible, reliability, responsiveness, assurance, and empathy, suggesting that the provided services do not meet student expectations. The dimension with the highest average gap was reliability (-0.52) and responsiveness (-0.40), underscoring the need for improvements in laboratory services. This study concludes that the role of laboratory staff is crucial in enhancing student satisfaction by identifying and addressing existing issues. It is hoped that with appropriate improvement efforts, the quality of computer laboratory services can be enhanced, leading to a better learning experience for students and increased satisfaction.